(untitled) (Research, Society and Development, 2021)
Objective of the present study is to present a clinical case of panfacial fracture with hybrid treatment through Rigid Internal Fixation and Semi Rigid Fixation of complex mandibular fracture. Female patient, 21 years old, feoderma, admitted to the ICU of Hospital Geral de Taipas after motorcycle accident, evaluated by the Buco Maxillofacial Surgery and Traumatology service in which she was diagnosed with panfacial fracture, with Le Fort I fractures, II, III, Lannelong, nasal fracture and complex mandibular fracture: right angle and left parasymphesis. The CT scan of the face confirmed the presence of Panfacial fracture. A tracheostomy surgical procedure was performed, plus the installation of an upper and lower Erich bar with closed reduction of the mandibular fracture with maxillary mandibular block with an elastic band in the first surgical period. After stabilization of the clinical picture, fixation of the mandibular fracture was performed through the accesses, submandibular and submental with FIR of the fracture of the right mandibular angle and Semi Rigid Fixation of the left parasymphysis fracture and mandibular maxillary block with elastic. The patient was transferred from the UTI to the ward where she was discharged from the hospital with satisfactory facial symmetry, Eagle Class I dental occlusion, preserved mandibular movements and complete absence after 7 months of signs and symptoms of paresthesia and neuropraxia of cranial nerves V and VII.